1997
DOI: 10.1136/oem.54.3.176
|View full text |Cite
|
Sign up to set email alerts
|

DNA single strand breakage, DNA adducts, and sister chromatid exchange in lymphocytes and phenanthrene and pyrene metabolites in urine of coke oven workers.

Abstract: Objectives-To investigate the specificity of biological monitoring variables (excretion of phenanthrene and pyrene metabolites in urine) and the usefulness of some biomarkers of effect (alkaline filter elution, 32p postlabelling assay, measurement of sister chromatid exchange) in workers exposed to polycyclic aromatic hydrocarbons (PAHs). Methods-29 coke oven workers and a standardised control group were investigated for frequencies of DNA single strand breakage, DNA protein cross links (alkaline filter elutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…Although the pack-years of cigarette smoking were significantly higher in the exposed group than in the control group, our results clearly showed that the difference in the DNA damage levels between the two groups was due to exposure to coke-oven emission, independent of smoking effects. This result was in agreement with most of the previously published studies (9,10,16). Although this study provided some new insight into the role of genetic polymorphisms in select PAH-metabolic genes in the formation of PAH-induced DNA damage in the coke-oven workers, the results are limited due to the relatively small sample size and the lack of data on other sources of PAHs, such as diet and passive smoking.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the pack-years of cigarette smoking were significantly higher in the exposed group than in the control group, our results clearly showed that the difference in the DNA damage levels between the two groups was due to exposure to coke-oven emission, independent of smoking effects. This result was in agreement with most of the previously published studies (9,10,16). Although this study provided some new insight into the role of genetic polymorphisms in select PAH-metabolic genes in the formation of PAH-induced DNA damage in the coke-oven workers, the results are limited due to the relatively small sample size and the lack of data on other sources of PAHs, such as diet and passive smoking.…”
Section: Discussionsupporting
confidence: 89%
“…It is thought that it is DNA damage, caused by reactive oxygen species formed during the metabolism of PAHs, that plays a role in PAH-induced carcinogenesis (6)(7)(8). Furthermore, the DNA damage caused by PAHs in coke-oven workers could be detected in their peripheral primary lymphocytes using the alkaline comet assay (9,10), whereas PAH-induced carcinogenesis could be modulated by genetic variation (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Coke oven emissions are a complex mixture of dusts, vapors, and gases. Mixed occupational exposure to PAHs has previously been investigated by many authors [Grimmer et al, 1993;Popp et al, 1997]. Jongeneelen et al [1988] suggest that 1-hydroxypyrene can be a useful refer-ence substance for biological monitoring of exposure to tar.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the glucuronide of 1-hydroxypyrene has also been used as an indicator of exposure, since the majority of 1-hydroxypyrene is conjugated and the fluorescence intensity of the conjugate is higher, but its additional value has not yet been assessed (Strickland et al, 1996). The measurement of various hydroxylated phenanthrenes has also been reported as a biomarker of exposure; analysis by GC-MS (Grimmer et al, 1991(Grimmer et al, , 1993 and HPLC has been used to measure hydroxylated phenanthrenes and 3-hydroxybenzo [a]pyrene (Gundel et al, 1996;Popp et al, 1997;Gendre et al, 2002). A recent attempt at immunoaffinity separation of PAH metabolites from the urine of exposed workers showed the presence of both 1-hydroxypyrene and several hydroxyphenanthrenes (Bentsen-Farmen et al, 1999).…”
Section: (C) Analysis Of Pah Metabolites In Urinementioning
confidence: 99%
“…Twenty-nine coke-oven workers and a control group were studied for frequencies of DNA single-strand breakage, DNA protein cross-links (alkaline filter elution assay), sister chromatid exchange and DNA adducts (measured by 32 Ppostlabelling analyses) in lymphocytes. While the frequency of DNA strand breaks in the lymphocytes of coke-oven workers was significantly higher than that in controls, the DNA adduct rate was not significantly increased in workers (Popp et al, 1997). Eightynine French coke-oven workers were compared with 44 power plant workers for antibenzo [a]pyrene -7,8-diol-9,10-oxide-DNA adduct levels and genetic polymorphisms to CYP1A1, GSTM1 and GSTT1 genes.…”
Section: (E) Coke Ovensmentioning
confidence: 99%